Structural health monitoring with piezoelectric wafer active sensors - Giurgiutiu, Victor (Elsevier/Academic Press, 2008)
Structural Health Monitoring (SHM) is the interdisciplinary engineering field devoted to the monitoring and assessment of structural health and durability. SHM technology integrates remote sensing, smart materials, and computer based knowledge systems to allow engineers see how built up structures are performing over time. It is particularly useful for remotely monitoring large infrastructure systems, such as bridges and dams, and high profile mechanical systems such as aircraft, spacecraft, ships, offshore structures and pipelines where performance is critical but onsite monitoring is difficult or even impossible. Structural Health Monitoring with Piezoelectric Wafer Active Sensors is the first comprehensive textbook to provide background information, theoretical modeling, and experimental examples on the principal technologies involved in SHM. This textbook can be used for both teaching and research. It not only provides students, engineers and other interested technical specialists with the foundational knowledge and necessary tools for understanding modern sensing materials and systems, but also shows them how to employ this knowledge in actual engineering situations.
Title from title screen.
Keywords: Structural analysis (Engineering); Automatic data collection systems.; Piezoelectric devices.; Piezoelectric transducers.; elektronické knihy; electronic books